Characteristics of Organic Fertilizer from Seaweed Sargassum sp. to Enhance the Growth of Caisim (Brassica juncea) Plants - Utami, Wina Nur Octavia; Pratama, Ginanjar; Hasanah, Afifah Nurazizatul (Jurnal Ilmiah PLATAX, 2026)
The use of organic fertilizer is an alternative to support sustainable agriculture because it can improve soil quality and reduce the use of chemical fertilizers. Sargassum sp. seaweed has the potential to be used as an organic fertilizer because it contains nutrients and plant growth hormones. This study aims to determine the characteristics of organic fertilizer derived from Sargassum sp. This study used a Completely Randomized Design with four treatments and three replications, namely W0 (100 mL commercial fertilizer), W1 (90 mL liquid fertilizer Sargassum sp.), W2 (100 mL liquid fertilizer Sargassum sp.), and W3 (110 mL liquid fertilizer Sargassum sp.). The fertilizer was produced through fermentation of Sargassum sp. The results showed that the liquid organic fertilizer produced a yield of 277.33%, pH 3.36–3.57, and nitrogen content of 0.03%. The W0 treatment produced the best growth compared to organic fertilizer Sargassum sp. The low nitrogen content and acidic pH are thought to affect the effectiveness of the fertilizer on plant growth. In conclusion, organic fertilizer Sargassum sp. has the potential to be an environmentally friendly fertilizer alternative, but optimization of the fermentation process and fertilizer formulation is still needed. Keywords: caisim, organic fertilizer, Sargassum sp.